Crankshaft’s machining process accuracy improvement by integrating DMAIC framework, Shainin Red X, and Taguchi Method - Agus Setyo Anto Wibowo; Yunita Umniyati; Aditya Tirta Pratama (JTTM : Jurnal Terapan Teknik Mesin, 2026)
This study investigates the problem of oversized hole diameter defects in crankshaft machining. The problem occurred in fine boring process which accounted for 42.3% of total rejections in the machining process. To systematically overcome this issue, a hybrid methodology was adopted by integrating 3 methods: Six Sigma’s DMAIC framework, Shainin Red X root cause analysis, and Taguchi Design of Experiments (DOE). By using multi-vari analysis and Red X techniques, the dominant cause of variation was identified as inconsistent tool offset input by operators, with secondary factors including clamper piston wear and part positioning misalignment. Taguchi DOE confirmed that depth of cut significantly influenced hole diameter accuracy, while spindle speed had minimal effect. The optimized machining parameters improved process capability, reducing rejection rates and cutting failure costs. The results show the synergy between diagnostic and optimization methods, providing a structured, data-driven framework for sustainable machining improvements. The novelty of this study lies in the integrated application of DMAIC, Shainin Red X, and Taguchi DOE to focus on oversized hole defects in crankshaft fine boring, an approach that has rarely been applied to turning-based off-center boring processes, with implications for both academic research and industrial precision machining practice.